Implementasi Harta Gono Gini Secara Hukum Islam Menurut Pandangan Masyarakat Desa Sangga Lima Kecamatan Gebang - Yuni Lestari; As’ad Badar (Journal Smart Law, 2023)
Scholars' studies on gono-gini have given rise to the opinion that gono-gini assets can be included as qiyas as syirkah. Mutual assets can be equated or classified into syirkah assets, namely assets accumulated during marriage must be divided proportionally in the event of a divorce. Wealth can be classified as qiyas with syirkah because it is understood that a wife can be counted as a working partner (share), even though she does not directly work in the real sense. The view of Islamic law allows a marriage agreement to be held before the marriage is carried out in the form of merging personal property of each into joint property, it can also be stipulated regarding the combination of the results of the private property of each husband and wife and it can also be stipulated that there is no merging of private property of each property. with husband and wife. Article 37 Law no. 1 of 1974 concerning Marriage and Articles 96 and Article 97 of the Compilation of Laws, it is stated that if a marriage is broken up either by divorce or by death, each husband and wife will receive half of the joint assets acquired during the marriage. This provision is in line with the Indonesian Supreme Court Jurisprudence No. 424.K/Sip.1959 dated December 9, 1959 which contains a legal abstraction that in the event of a divorce, each party (husband and wife) gets half of their joint property (gono-gini).Respondents conducted interviews regarding the divorce has been carried out through the mechanism of the religious court. However, there is no discussion of the division of joint assets during divorce in court so that the process of sharing joint assets is carried out with each other's understanding without a court process so that one party is still dissatisfied but they do not take steps to settle it in a religious court. After there was no common ground, one of the respondents submitted a request to the religious court for the distribution of joint assets, but at the time of the research, there was no court decision because the court was still handling the process regarding the distribution of the house currently occupied by his ex-wife. Community leaders interviewed by researchers who work as the teacher provides good knowledge regarding the distribution of assets going back and forth because of his education and experience seeing the conditions of the surrounding community. He explained that joint property is property acquired after marriage and must be divided according to the provisions of each half of the property. Meanwhile, inherited assets cannot be divided because they are assets acquired prior to the marriage and are fully the rights of each, unless there is a prior agreement.